Teachers' ability to design islamic religious education learning media using the powerdirector application at the darul mahfudz islamic boarding school, lekopadis - Andi Kurnia Muin; Hanafi Pelu (Balai Diklat Keagamaan Ambon, 2024)
The purpose of this article is to explain the teacher's ability to design Islamic Religious Education learning media using the PowerDirector application at the Darul Mahfudz Islamic Boarding School. The research method used in this article is qualitative, while the type of research used in this article is descriptive research. The research results show that; Islamic Religious Education subject teachers have been able to use the PowerDirector application, by utilizing available resources such as tutorials or online guidebooks, and collaborating with other educators to share experiences and references to improve educators' skills in designing Islamic Religious Education teaching materials, by using media using the PowerDirector application. Apart from that, using the PowerDirector program in learning can help students improve their ability to express opinions and write various kinds of assignments submitted by their teachers by developing learning media and communication skills in Islamic Religious Education subjects. As a result, the PowerDirector program can be a useful tool for creating interesting and effective learning videos for students.